The association of plasma connective tissue growth factor levels with left ventricular diastolic dysfunction in patients with overt hyperthyroidism - Li, Huan; Ren, Yahui; Wang, Linfang; Li, Yuming (Frontiers in Endocrinology, 2024)
Background Left ventricular (LV) diastolic dysfunction is an independent predictor of future cardiovascular events. Early detection of patients with LV diastolic dysfunction can improve clinical outcomes through active management. However, the assessment of diastolic function is very complicated, and there are currently lack of effective biomarkers to assess the risk of LV diastolic dysfunction. Connective tissue growth factor (CTGF) plays a significant role in cardiac remodeling and dysfunction. We aimed to investigate the associations between plasma CTGF level and the risk of LV diastolic dysfunction in this study and judge its effectiveness in diagnosing LV diastolic dysfunction. Methods A total of 169 patients with overt hyperthyroidism were included. LV diastolic function was evaluated and the subjects were divided into normal LV diastolic function group and LV diastolic dysfunction group. Routine clinical medical data, biochemical data, thyroid related parameters and echocardiographic parameters were recorded for analysis. Results Compared with normal LV diastolic function group, the LV diastolic dysfunction group had higher age and BMI, as well as lower heart rate, lower serum albumin, lower eGFR, higher serum TgAb and BNP level, and the incidences of hypertension were also higher (all P <0.05). Circulating plasma CTGF levels in the LV diastolic dysfunction group were significantly higher (normal LV diastolic function group: 7.026 [5.567-8.895], LV diastolic dysfunction group: 8.290 [7.054-9.225] ng/ml, median [(Interquartile range)], P = 0.004); Compared with the lowest quartile group, the crude odds ratios (OR) of LV diastolic dysfunction in the second, third, and fourth quartile group were 3.207, 5.032 and 4.554, respectively (all P<0.05). After adjustment for the potentially confounding variables, the adjusted OR values of the third and fourth quartile group had no obvious change. The results of ROC showed that the plasma CTGF had the largest area under the ROC curve, and the value was 0.659 (P = 0.005). Conclusion The level of circulating plasma CTGF in the LV diastolic dysfunction group was significantly increased. Plasma CTGF level is an independent risk factor for LV diastolic dysfunction. Compared with serum BNP level, the plasma CTGF level may have auxiliary diagnostic value for LV diastolic dysfunction in hyperthyroid patients.